Use of kidney failure risk equation to predict progression of end-stage renal failure in Turkish patients with stage 3–4 chronic kidney disease (Annals of Medical Research, 2024)
Aim: The Kidney Failure Risk Equation (KFRE) is a useful tool for predicting chronic kidney disease (CKD) progression to end-stage renal disease (ESRD). It has been validated in various  populations. This study aimed to evaluate the prognostic significance of the KFRE model in a Turkish CKD cohort.Materials and Methods: In a prior retrospective study at a single center, the 4-variable KFRE model's accuracy in predicting ESRD progression was assessed. Among 246 stage 3 or 4 CKD individuals, two-year risk predictions categorized participants into low-intermediate (
Keywords: Chronic kidney disease; Kidney failure risk equation; Turkey